Redefining Cybersecurity through Processual Ontology of the Cyberspace - Robert Siudak (Ksiegarnia Akademicka Publishing, 2021)
The way cyberspace is conceptualized in security discourses shapes strategies, tools and possible solutions developed within the ICT security debate. Putting forward processual ontology of cyberspace helps in apprehending the unique dynamics of this new domain arising from the intersection of ICT with social and political phenomena. Cyberspace is presented as a process of data transmission and information cognition/processing in the digital domain. It contains time as an inherent dimension and includes all subjects and objects of this process: data (codes, packets, files, texts), information (structured or operationalized data), human and computer agents (people, software) and communication environment (hardware, protocols). Processual ontology is based on the fact that ICT is a man-made realm with almost unlimited potential to expand, where physical distance is lapsed and bits are the primary matter. This theoretical stance blurs the line between human and non-human agents, dehumanizing the idea of actorness by categorizing both humans and computers as actors. Finally, processual ontology of cyberspace promotes resilience strategies both in the private sector as well as on national and international level.